BIG DATA ANALYSIS IN HUMAN RESOURCES DECISION MAKING: OPTIMIZING WORKFORCE MANAGEMENT - Heliana; Wahyuni, Herpita (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2024)
This research aims to conduct an in-depth analysis of the application of Big Data in human resource decision-making, focusing on optimizing workforce management. By measuring four main variables, namely recruitment efficiency, accuracy of employee selection, employee development, and organizational performance based on HR decision-making—Big Data analysis is expected to provide a deeper understanding of workforce dynamics. The research results show that applying Big Data can build recruitment efficiency, increase the accuracy of employee selection, support more appropriate employee development, and ultimately improve overall organizational performance. Big Data makes organizational performance based on HR decision-making by providing a solid foundation for more effective human resource management strategies. This research uses qualitative methods with the help of the NVivo 12 Plus tool to identify research results. Implementing Big Data in various aspects of human resource management is recognized as a catalyst for positive change in workforce management.